The role of women smallholder farmers in achieving global food security: an overview - Muchiri, Caroline; Lecoutere, Els; Haan, Nicoline C. de (Burleigh Dodds Science Publishing Limited, 2025)
Women smallholder farmers across the globe play pivotal roles in enhancing global food security by contributing to food production, accessibility, stability and utilisation. These roles lack sufficient recognition in global food policies and are hindered by prevailing structural gender inequalities. These constraints are rooted in restrictive gender norms, disparities in access to and control over productive and complementary resources, disproportionate allocation of domestic responsibilities and limited agency. They collectively undermine the full potential of women’s contributions to sustainable food security. Challenging the discriminatory norms that weaken women’s capacities to produce and purchase sufficient and nutritious food requires targeted strategies to promote gender equality and empower women to achieve improved food security outcomes at the household, community and global levels. Accessing data from global datasets about women's contributions and challenges offers the necessary evidence to support their crucial role in attaining food security.